Determinants of Capital Structure: A Study of Listed Manufacturing Companies of Colombo Stock Exchange (CSE), Sri Lanka - Yogendrarajah, R.; Thanabalasingam, S. (International Conference on Financial Information and Strategies at Annamalai University, India – 2011., 2011)
This study examines the determinants of capital structure decisions of firms, specifically for manufacturing companies. The survey data were gathered from listed companies from stock exchange in Sri Lanka. The capital structure is the composition of debt and equity capital that comprises a firm’s financing its assets. In this study an attempt has been made to examine what factors determine the capital structure of the listed manufacturing companies in Sri Lanka. For this purpose 5 years data from 2005 to 2009 have been gathered from the Colombo Stock Exchange (CSE). The capital structure was represented by the leverage and the profitability, tangibility and the asset turnover have been selected as the determinant factors of Capital Structure. The data were analyzed using descriptive and inferential statistics. Finding of this study revealed that there is low relationship between the factors of leverage and profitability. Based on this study, tangibility and asset turnover has negative relationship related with leverage. And it showed the impact of profitability, tangibility and asset turnover on leverage was only 10%, 2% and 1% respectively and profitability has the most impact on Leverage than other factors of tangibility and asset turnover. The factors other than profitability, tangibility and asset turnover mostly influence on capital structure.
Keywords: Capital structure; Profitability; Tangibility; y, Colombo Stock Exchange (CSE); Leverage